Improving acne keloidalis nuchae with targeted ultraviolet B treatment: a prospective, randomized, split‐scalp comparison study. (1st November 2014) - Okoye, G.A.; Rainer, B.M.; Leung, S.G.; Suh, H.S.; Kim, J.H.; Nelson, A.M.; Garza, L.A.; Chien, A.L.; Kang, S.
Summary: Background: Acne keloidalis nuchae (AKN) is a chronic scarring folliculitis with fibrotic papules on the occipital scalp. Its treatment is limited and unsatisfactory. Objectives: To determine whether targeted ultraviolet B (tUVB) phototherapy will (i) improve the clinical appearance of AKN and (ii) induce extracellular matrix remodelling in affected lesions. Methods: Eleven patients with AKN were enrolled in a prospective, randomized, split‐scalp comparison study. One randomly selected side of the scalp was treated with tUVB up to three times weekly for 8 weeks. After week 8, both sides were treated for eight additional weeks. Assessment included lesion counts in two 3 × 3‐cm regions of interest (ROIs), one on each side of the scalp (ROI‐1: tUVB weeks 0–16, ROI‐2: tUVB weeks 9–16), patient self‐assessment and analysis of MMP1, MMP9, TGFB1 and COL1A1 mRNA expression by quantitative reverse‐transcription polymerase chain reaction. Results: Before treatment, the mean lesion count was similar between tUVB‐treated and untreated sides (14·8 vs. 15·0). After 8 weeks of tUVB, the mean lesion count decreased significantly to 9·4 ± 1·2 ( P = 0·03), with no change on the untreated side. With continued treatment, the mean lesion count in ROI‐1 decreased further to 7 ± 1·5 ( P = 0·04) after 16 weeks of tUVB. Conclusions: tUVB significantly improved the clinical appearance of AKN, led to patient satisfaction and was well tolerated.